MAKNA WADAH DALAM UPACARA NGABEN PRATISENTANA ARYA GAJAH PARA - I Gede Satria Budhi Utama; I Wayan Arissusila; IB Eka Sutha Harunika (WIDYANATYA, 2022)
The container in Indonesian is a means of conveying the corpse in the Ngaben ceremony in Bali. The shape and structure of the container is strongly influenced by the soroh or community groups. One of the many types of containers in Bali is the winged container used by Pratisantana Arya Gajah Para in the village of Loaddem. The reason for the use of the Wadah in the Ngaben Pratisentana Arya Gajah Para ceremony in the village of Loaddem is due to the combination of Gamapati inherited by the ancestors of Sira Arya Gajah Para which was then combined with the village Dreshta which is a local belief in the village of Loaddem, District of Loaddem, Regency of Karangasem. 2. The form of the container used in the Ngaben Pratisentana Arya Gajah Para ceremony in the village of Loaddem is a winged container using Boma, Wilmana, Garuda Mungkur corals as a complement. There are several kinds of pepalihan that are applied in the embodiment of this container, including: palih Bacem, Gunung tajak, palih taman, sancak, Bada dara, and rongan, which in each area are decorated with various kinds of ornaments such as keketusan, pepatran, and authorship. ABSTRAK Wadah dalam Bahasa Indonesia adalah merupakan sarana pengantar jenazah dalam upacara Ngaben di Bali. Bentuk dan struktur bangun pada wadah sangat dipengaruhi oleh soroh atau kelompok warga. Salah satu dari sekian banyaknya jenis Wadah di Bali adalah Wadah Bersayap yang digunakan oleh Pratisantana Arya Gajah Para di desa Bebandem. Alasan dari penggunaan Wadah dalam upacara Ngaben Pratisentana Arya Gajah Para di desa Bebandem adalah berkat adanya gabungan antara Gamapati yang diwariskan oleh leluhur Sira Arya Gajah Para yang kemudian digabungkan dengan Dreshta desa yang merupakan kepercayaan lokal yang ada di desa Bebandem, Kecamatan Bebandem, Kabupaten Karangasem. 2. wujud dari Wadah yang dipakai dalam upacara Ngaben Pratisentana Arya Gajah Para di desa Bebandem adalah Wadah bersayap dengan memakai karang Boma, Wilmana, Garuda mungkur sebagai pelengkapnnya. Adapun beberapa macam pepalihan yang diterapkan dalam perwujudan Wadah ini antara lain: palih Bacem, Gunung tajak, palih taman, sancak, Bada dara, dan rongan, yang di setiap bidangnya dihias dengan berbagai macam ornamen seperti keketusan, pepatran, dan kekarangan.